2018
DOI: 10.1111/all.13630
|View full text |Cite
|
Sign up to set email alerts
|

Atopic diseases and type I sensitization from adolescence to adulthood in an unselected population (TOACS) with focus on predictors for allergic rhinitis

Abstract: Background: While much is known on childhood atopic diseases, knowledge about persistence of atopic diseases from childhood to adulthood is limited. We therefore aimed to study the clinical course of atopic diseases and type I sensitization prospectively in an unselected cohort of adolescents followed into adulthood.Methods: A cohort of unselected 8th-grade school children (mean age 14 years) established in 1995 and followed up in 2010 were evaluated with questionnaire, clinical examination, skin prick tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…The paucity of data about NAC safety and reproducibility might also account for this low implementation. Nevertheless, the description of allergic phenotypes of rhinitis without systemic atopy (LAR) and the progressively increasing prevalence of AR patients with multiple positive SPTs indicate the need to include NAC in the diagnostic work‐up of rhinitis patients . In this regard, our group described a shortened protocol (NAC‐M) to test multiple allergens in a single session, and demonstrated its good diagnostic performance in LAR patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paucity of data about NAC safety and reproducibility might also account for this low implementation. Nevertheless, the description of allergic phenotypes of rhinitis without systemic atopy (LAR) and the progressively increasing prevalence of AR patients with multiple positive SPTs indicate the need to include NAC in the diagnostic work‐up of rhinitis patients . In this regard, our group described a shortened protocol (NAC‐M) to test multiple allergens in a single session, and demonstrated its good diagnostic performance in LAR patients …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a proportion of healthy subjects also display positivity for either test . Additionally, in many AR patients it is difficult to establish the clinical relevance of IgE‐sensitizations due to a lack of consistency with the symptom pattern, or due to multiple positive SPTs . In these situations, it is challenging to design the composition of allergen immunotherapy (AIT) .…”
Section: Introductionmentioning
confidence: 99%
“…46 Indeed, many adolescent individuals are asymptomatic and develop AR in adulthood. 47 Diet is also related to AR, and studies have indicated that dietary changes can lead to increased incidence of allergic diseases and asthma. 48 Similarly, changes in environmental factors, such as temperature and climate change, can lead to changes in allergens such as pollen, which can induce or aggravate the symptoms of AR.…”
Section: Other Risk Factors Of Armentioning
confidence: 99%
“…Allergic rhinitis (AR) is a chronic inflammatory disease of the lining of nasal mucosa induced by type I hypersensitivity response upon exposure to common inhaled allergens in sensitized individuals [1]. AR affects up to 40% of worldwide population with an increasing prevalence over the past 20 years [2][3][4][5][6][7][8]. It is associated with significantly lower quality of life due to impaired sleep, learning difficulties, deterioration of at-work performance and social functioning, which highlights AR as a substantial economic burden and a serious global health problem [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%